ASSOCIATION BETWEEN PSORIASIS AND COELIAC DISEASE RELATED ANTIBODIES - Khan, Jauhar Mumtaz; Rao, Sibghat Ullah; Rathore, Muhammad Usman; Janjua, Wasif (Journal of Ayub Medical College Abbottabad, 2014)
Background: Psoriasis is a common, chronic, disfiguring, inflammatory and proliferative condition of skin manifested by red, scaly, sharply demarcated, indurated plaques present particularly over the extensor surfaces and scalp. The disease has been found to be associated with celiac disease related antibodies with variable frequencies in different populations of the world. The subset of patients showing this association have a higher psoriasis severity and also respond well to cost effective way of gluten free diet. There is a need to work out the frequency of these antibodies in our local psoriatic patients. Methods: The study was carried out in Department of Dermatology, Military Hospital Rawalpindi from 4th June to 4th December, 2008. A total of 80 patients of both gender, aged more than 15 with a clinical diagnosis of psoriasis attending dermatology outpatient department were selected. Relevant history and thorough physical examination was performed and disease characteristics like previous treatments received and history of arthropathy were obtained. Coeliac disease related antibodies were assessed on serum by indirect immunofluorescence and data was analysed using software SPSS-13. Results: From the study of 80 patients, celiac disease related antibodies were found in none of the cases. All the severe and mild to moderate patients of psoriasis were negative for IgA antigliadin antibodies, IgG antigliadin antibodies and IgA anti-reticulin antibody. Conclusion: This study concludes that celiac disease related antibodies are not present in psoriatic patients irrespective of severity of disease in our local population. Keywords: Psoriasis, coeliac disease, celiac disease associated antibodies, gluten free diet